BRINE SHRIMPS LETHALITY TEST OF ETHANOL EXTRACT AND GAS CHROMATOGRAPHY-MASS SPECTROMETRY ANALYSIS OF ETHYL ACETATE FRACTION OF BLIGHIA SAPIDA - MB, ADEKOLA; JO, AREOLA; OV, ORIYOMI; JT, APATA; OE, APALOWO; AF, ADESINA; OO, BABALOLA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to evaluate brine shrimp lethality of Blighia sapida stem-bark extract and its fractions and identify the bioactive constituents in the ethyl acetate fraction (EAF) using gas chromatography-mass spectrometry (GC-MS) technique. Methods: The ethanol extract (EE) and its fractions were subjected to lethality assay, and GC-MS analysis of EAF was carried out. Results: The lethality test showed a concentration-dependent mortality rate in the brine shrimp nauplii for the EE and its fractions. GC-MS analysis of EAF of the extract revealed the existence of 13 peaks of the GC-MS chromatogram with only one prominent compound, n-hexadecanoic acid (peak area of 10.13%). Conclusion: The result revealed the presence of 13 bioactive components in the EAF of the extract, the majority of which have been reported for different biological activities, hence, justifies the use of the plant in the treatment and management of different diseases ethnomedicinally.